On some morphologically aberrant, auto-epizootic forms of Plumularia setacea (Linnaeus, 1758) (Cnidaria: Hydrozoa) from southern Chile - Galea, Horia R.; Leclère, Lucas (Zootaxa, 2007)
Several peculiar, auto-epizootic forms of Plumularia setacea (Linnaeus, 1758) are described from southern Chile. They live exclusively on normal stems of the same species and are characterized by a remarkable stunting of the colonies, which possess very short cladia composed of only one hydrotheca, with one of the lateral nematothecae often absent. Single cladia arising directly from the hydrorhiza, or aberrant ramifications of the stem and/or branches, have also been observed. The morphological features of these epizootic forms are described in detail and compared with those of normal specimens of P. setacea. Differences with related epizootic colonies, reported from various localities around the world, are also discussed. A comparison of the mitochondrial 16S rRNA of both epizootic and normal forms showed that the former is closely-related to its normal counterpart and probably belongs to the same species.